A combination of the identifcation algorithm and the modal superposition method for feedback active control of incomplete measured systems - Anh, N. D.; Viet, L. D. (VNU Journal of Science: Mathematics - Physics, 2007)
Abstract. In a previous paper [1], the identiíication algorithm is presented for feedback active controlled systems. However, this method can only be appỉied to complete measured systems. The aim o f this paper is to present a combination o f the identification algorithm and the modal superposition method to control the incomplete measured systems. The system response is expanded by modal eigenfiinction technique. The extemaỉ excitation acting on some íĩrst modes is identiíìed vvith a time delay and vvith a small error depending on the ỉocations o f the sensors. Then the control forces vvill be generated to balance the identiíĩed excitations. A numerical simulation is applied to a building modeled as a cantilever beam subjected to base acceleration.